Trade, the WTO and Energy Security
XI, 182 p. 3 illus. in color.
Keywords: The linkages between WTO rules governing trade and energy security – with a certain degree of focus on India – are the main subject of this book. The edited volume brings together the views of academics, policymakers and experts with extensive experience covering WTO and international trade issues. The issues examined include mapping the linkages between trade and energy security in the WTO agreements, case law, accession and Doha negotiations; assessing the issues that could be raised by energy deficit or energy surplus countries at the WTO; analyzing the provisions of the ECT and NAFTA vis-à-vis the Indian policy framework; and examining the trade regimes of selected OPEC members and other major suppliers of fossil fuels to India. While the Indian perspective is evident in the contributions, this book will also be of interest to an international audience, as trade, the WTO and energy security are global concerns and of relevance to all practitioners and academics working on these issues.